2018
DOI: 10.1158/1541-7786.mcr-17-0146
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale RNAi Screen Identifies SGK1 as a Key Survival Kinase for GBM Stem Cells

Abstract: Glioblastoma multiforme (GBM) is the most common type of primary malignant brain cancer and has a very poor prognosis. A subpopulation of cells known as GBM stem-like cells (GBM-SC) have the capacity to initiate and sustain tumor growth and possess molecular characteristics similar to the parental tumor. GBM-SCs are known to be enriched in hypoxic niches and may contribute to therapeutic resistance. Therefore, to identify genetic determinants important for the proliferation and survival of GBM stem cells, an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Gliomas are tumors originating mostly from the brain glial cells that include the glioblastoma multiforme (GBM) (WHO grade IV gliomas) as well as other low‐grade gliomas. GBMs are the most frequent, malignant and aggressive subtypes of glioma, with exceedingly high relapse and poor prognosis, because GBM progenitor cells with tumor‐precursors are resistant to radiation and chemotherapy Devastating glioma cells show fast infiltration and hide in inaccessible areas of brain, which rules out the possibility of surgery, and radiation methods . Chemotherapy fails in most of the GBM patients since most drugs are incapable of crossing the BBB and arriving at tumor tissues .…”
Section: Applications Of Msnsmentioning
confidence: 99%
“…Gliomas are tumors originating mostly from the brain glial cells that include the glioblastoma multiforme (GBM) (WHO grade IV gliomas) as well as other low‐grade gliomas. GBMs are the most frequent, malignant and aggressive subtypes of glioma, with exceedingly high relapse and poor prognosis, because GBM progenitor cells with tumor‐precursors are resistant to radiation and chemotherapy Devastating glioma cells show fast infiltration and hide in inaccessible areas of brain, which rules out the possibility of surgery, and radiation methods . Chemotherapy fails in most of the GBM patients since most drugs are incapable of crossing the BBB and arriving at tumor tissues .…”
Section: Applications Of Msnsmentioning
confidence: 99%
“…The unique capacity of SGK1 to promote enhanced glucose uptake during ECM-detachment suggests that SGK1 signaling may be disproportionately important when cells encounter distinct stresses. Indeed, recent studies have demonstrated that SGK1 can promote resistance to chemotherapies and contribute to oncogenic transformation (Castel et al, 2016;Kulkarni et al, 2018;Ma et al, 2019;Orlacchio et al, 2017) suggesting that SGK1 signaling is valuable for navigating stressful environments. 18 SGK1 has long been known to function as an effector of PI(3)K signaling in a fashion that can be analogous to Akt.…”
Section: Discussionmentioning
confidence: 99%
“…They found that SGK1 depletion and inhibition has little effect on serum grown glioma lines and on differentiated GBM stem-like cells, indicating its specific importance in GBM stem-like cell survival only on glioblastoma cells interacting with multiple other genes. Kulkarni et al validated SGK1 as critical for GBM stem-like cell proliferation and survival, using shRNA, CRISPR and an SGK1-specific inhibitor (5).…”
Section: Discussionmentioning
confidence: 99%
“…Kulkarni et al have reported that the serum and glucocorticoid-regulated kinase (SGK1) gene is required for the growth and survival of GBM stem-like cells under both normoxic and hypoxic conditions (5). In this analysis, we examined the role of the SGK1 gene in glioblastoma survival to determine if it might be a potential drug target.…”
Section: Abstract Background/aim: Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%